Reversing EGFR Mediated Immunoescape by Targeted Monoclonal Antibody Therapy - Concha-Benavente, Fernando; Ferris, Robert L. (Frontiers in Pharmacology, 2017)
Uncontrolled growth is a signature of carcinogenesis, in part mediated by overexpression or overstimulation of growth factor receptors. The epidermal growth factor receptor (EGFR) mediates activation of multiple oncogenic signaling pathways and escape from recognition by the host immune system. We discuss how EGFR signaling downregulates tumor antigen presentation, upregulates suppressive checkpoint receptor ligand programmed death ligand (PD-L1), induces secretion of inhibitory molecules such as transforming growth factor beta (TGF) and reprograms the metabolic pathways in cancer cells to upregulate aerobic glycolysis and lactate secretion that ultimately lead to impaired cellular immunity mediated by natural killer (NK) cell and cytotoxic T lymphocytes (CTL). Ultimately, our understanding of EGFR-mediated escape mechanisms has led us to design EGFR-specific monoclonal antibody therapies that not only inhibit tumor cell metabolic changes and intrinsic oncogenic signaling but also activates immune cells that mediate tumor clearance. Importantly, targeted immunotherapy may also benefit from combination with antibodies that target other immunosuppressive pathways such PD-L1 or TGF and ultimately enhance clinical efficacy.